Enhanced proliferation of PC12 neural cells on untreated, nanotextured glass coverslips. (6th September 2016) - Islam, Muhymin; Atmaramani, Rahul; Mukherjee, Siddhartha; Ghosh, Santaneel; Iqbal, Samir M
Abstract: Traumatic injury to the central nervous system is a significant health problem. There is no effective treatment available partly because of the complexity of the system. Implementation of multifunctional micro- and nano-device based combinatorial therapeutics can provide biocompatible and tunable approaches to perform on-demand release of specific drugs. This can help the damaged cells to improve neuronal survival, regeneration of axons, and their reconnection to appropriate targets. Nano-topological features induced rapid cell growth is especially important towards the design of effective platforms to facilitate damaged neural circuit reconstruction. In this study, for the first time, feasibility of neuron-like PC12 cell growth on untreated and easy to prepare nanotextured surfaces has been carried out. The PC12 neuron-like cells were cultured on micro reactive ion etched  nanotextured glass coverslips. The effect of nanotextured topology as physical cue for the growth of PC12 cells was observed exclusively, eliminating the possible influence(s) of the enhanced concentration of coated materials on the surface. The cell density was observed to increase by almost 200% on nanotextured coverslips compared to plain coverslips. The morphology study indicated that PC12 cell attachment and growth on the nanotextured substrates did not launch any apoptotic machinery of the cell. Less than 5% cells deformed and depicted condensed nuclei with apoptotic bodies on nanotextured surfaces which is typical for the normal cell handling and culture. Enhanced PC12 cell proliferation by such novel and easy to prepare substrates is not only attractive for neurite outgrowth and guidance, but may be used to increase the affinity of similar cancerous cells (ex: B35 neuroblastoma) and rapid proliferation thereafter—towards the development of combinatorial theranostics to diagnose and treat aggressive cancers like neuroblastoma.